Safety and tolerability results of atogepant for the preventive treatment of episodic migraine from a 40-week, open-label multicenter extension of the phase 3 ADVANCE trial. (January 2023) - Klein, Brad C; Miceli, Rosa; Severt, Lawrence; McAllister, Peter; Mechtler, Laszlo; McVige, Jennifer; Diamond, Merle; Marmura, Michael J; Guo, Hua; Finnegan, Michelle; Trugman, Joel M
Background: Atogepant is a United States Food and Drug Administration-approved oral calcitonin gene-related peptide receptor antagonist for the preventive treatment of episodic migraine. The study objective was to evaluate the long-term safety and tolerability of atogepant in participants who completed the phase 3 ADVANCE trial (NCT03777059). Methods: This 40-week, open-label extension trial (NCT03939312) monitored safety in participants receiving oral atogepant 60 mg once daily, followed by a four-week safety follow-up period. Results: Of the 685 participants taking at least one dose of atogepant, the treatment period was completed by 74.6% of participants with a mean (standard deviation) treatment duration of 233.6 (89.3) days. Treatment-emergent adverse events occurred in 62.5% of participants, with upper respiratory tract infection (5.5%), urinary tract infection (5.3%), nasopharyngitis (4.8%), sinusitis (3.6%), constipation (3.4%), and nausea (3.4%) occurring at ≥3%. Serious adverse events were observed in 3.4% of participants (none were treatment-related), and there were no deaths. Adverse events leading to discontinuation occurring at >0.1% were nausea (0.4%) and abdominal pain, vomiting, weight decrease, dizziness, and migraine (0.3% each). Conclusion: These results are consistent with atogepant's known safety profile and support long-term use of atogepant 60 mg once daily dosing as safe and well tolerated. ClinicalTrials.gov Registration Number: NCT03939312